Atmospheric radiation modeling of galactic cosmic rays using LRO/CRaTER and the EMMREM model with comparisons to balloon and airline based measurements. Issue 9 (10th September 2016) - Joyce, C. J.; Schwadron, N. A.; Townsend, L. W.; deWet, W. C.; Wilson, J. K.; Spence, H. E.; Tobiska, W. K.; Shelton‐Mur, K.; Yarborough, A.; Harvey, J.; Herbst, A.; Koske‐Phillips, A.; et al.
Abstract: We provide an analysis of the galactic cosmic ray radiation environment of Earth's atmosphere using measurements from the Cosmic Ray Telescope for the Effects of Radiation (CRaTER) aboard the Lunar Reconnaissance Orbiter (LRO) together with the Badhwar‐O'Neil model and dose lookup tables generated by the Earth‐Moon‐Mars Radiation Environment Module (EMMREM). This study demonstrates an updated atmospheric radiation model that uses new dose tables to improve the accuracy of the modeled dose rates. Additionally, a method for computing geomagnetic cutoffs is incorporated into the model in order to account for location‐dependent effects of the magnetosphere. Newly available measurements of atmospheric dose rates from instruments aboard commercial aircraft and high‐altitude balloons enable us to evaluate the accuracy of the model in computing atmospheric dose rates. When compared to the available observations, the model seems to be reasonably accurate in modeling atmospheric radiation levels, overestimating airline dose rates by an average of 20%, which falls within the uncertainty limit recommended by the International Commission on Radiation Units and Measurements (ICRU). Additionally, measurements made aboard high‐altitude balloons during simultaneous launches from New Hampshire and California provide an additional comparison to the model. We also find that the newly incorporated geomagnetic cutoff method enables the model to represent radiation variability as a function of location with sufficient accuracy. Key Points: We demonstrate an improved model of the Earth's radiation environment and compare it to airline and balloon based measurements We find the model to be sufficiently accurate to assess radiation risks in Earth's atmosphere This model will be made available to the community for future efforts in risk assessment and the study of atmospheric radiation